Structure and Written Expression Section on Paper-Based TOEFL : Perceived Difficulties by Nursing Students of Poltekes Solok, West Sumatera - Handayani, Fitri (Jurnal Educative: Journal of Educational Studies, 2019)
English language ability is one of the skills that must be possessed by college students, including nursing students. Having good English skills will open broad opportunities for increasing the competency and expertise of nursing students. One form of recognition of good English skills is to have a high TOEFL score. However, getting a high TOEFL score is still a challenge for nursing students. Facts in the field show that many nursing students find it difficult to achieve high scores on the TOEFL test. The most common form of difficulty is the problem in answering questions related to the structure and written expression section in the Paper-Based TOEFL test. The purpose of this research is to investigate nursing students’ difficulties in the structure and written expressions section tested in the Paper-Based TOEFL. The population of this study was 80 nursing students of POLTEKES Solok, and the sample was selected by using cluster random sampling. Data of the research was collected through tests and interviews. The result of the research found that that there were 8 items considered as the most difficult elements met by nursing students in the TOEFL test. These items were word order, parallel structure, singular and plural nouns, missing and extra words, articles, comparative and superlative, word choice, and word form. In addition, the findings also show that several factors influence nursing students' difficulties in the structure and written expression section. The factors were unfamiliarity with the TOEFL test, lack of practice, and lack of grammatical competence. Kemampuan berbahasa Inggris merupakan salah satu keterampilan yang harus dimiliki oleh mahasiswa perguruan tinggi, termasuk mahasiswa keperawatan. Dengan memiliki keterampilan bahasa Inggris yang baik akan membuka kesempatan yang luas terhadap peningkatan kompetensi dan keahlian mahasiswa keperawatan. Salah satu bentuk pengakuan dari kemampuan bahasa Inggris yang baik ialah memiliki skor TOEFL yang tinggi. Namun, mendapatkan nilai yang tinggi dalam test TOEFL masih menjadi tantangan tersendiri bagi mahasiswa keperawatan. Fakta di lapangan menunjukkan bahwa masih banyak mahasiswa keperawatan yang kesulitan untuk bisa mencapai skor tinggi dalam tes TOEFL. Bentuk kesulitan yang paling banyak ditemui adalah permasalahan dalam menjawab soal yang berkaitan dengan structure dan written expression section pada Paper-Based TOEFL test. Penelitian ini bertujuan untuk menyelidiki kesulitan yang dihadapi oleh mahasiswa keperawatan POLTEKES Solok dalam menjawab structure dan written expression section yang diuji dalam Paper-Based TOEFL. Populasi penelitian ini adalah 80 orang mahasiswa keperawatan, dan sampel penelitian ini dipilih dengan menggunakan cluster random sampling. Data dari penelitian ini dikumpulkan dengan menggunakan tes dan interview. Dari temuan penelitian, dapat disimpulkan bahwa ada 8 item yang dianggap sebagai elemen paling sulit yang ditemui mahasiswa keperawatan dalam tes TOEFL. Item-item tersebut adalah word order, parallel structure, singular and plural noun, missing dan extra words, article, comparative and superlative, word choice, dan word form.Selain itu, temuan ini juga menunjukkan bahwa ada beberapa faktor yang mempengaruhi kesulitan siswa dalam structure and written epression section. Faktor-faktor tersebut adalah tidak terbiasa dengan tes TOEFL, kurangnya latihan, dan kurangnya penguasaan tata bahasa. Kata Kunci: TOEFL, Structure and Written Expression Section, Mahasiswa Keperawatan